In Vitro Anti‐Inflammatory Activity of Selected Oxalate‐Degrading Probiotic Bacteria: Potential Applications in the Prevention and Treatment of Hyperoxaluria. Issue 3 (28th January 2014) - Giardina, Silvana; Scilironi, Cristina; Michelotti, Angela; Samuele, Alberta; Borella, Fabio; Daglia, Maria; Marzatico, Fulvio
Abstract Oxalate (Ox) is a very common component of the human diet, capable to collect in the renal tissue and bind calcium to form calcium oxalate (CaOx) crystals. A supersaturation of CaOx crystal may cause nephrocalcinosis and nephrolithiasis. The inflammation derived from the CaOx crystal accumulation, together with innate or secondary renal alterations, could strongly affect the renal function. In this case a consumption of probiotics with either oxalate‐degrading activity at intestinal level and systemic anti‐inflammatory activity could be an alternative approach to treat the subjects with excess of urinary oxalate excretion. 11 strains of lactic acid bacteria (Lactobacilli and Bifidobacteria), already included in the list of bacteria safe for the human use, were investigated for their capability to degrade oxalate by mean of RP‐HPLC‐UV method and modulate inflammation in an in vitro model system based on peripheral blood mononuclear cells. Four promising bacterial strains (Lactobacillus plantarum PBS067, Lactobacillus acidophilus LA‐14, Bifidobacterium breve PBS077, Bifidobacterium longum PBS078) were identified as innovative biological tools for the prevention and the therapeutic treatment of hyperoxaluria and the inflammatory events associated to the Ox accumulation. Practical Application The oxalate‐degrading activity of some probiotics and their capability to modulate the release of inflammation mediators could be exploited as a new nutraceutical and therapeutic approach for the treatment of oxalate accumulation and the related inflammatory state.